Association between problem gambling and personality traits: a longitudinal study among the general Norwegian population - Kaur, Puneet; Leino, Tony; Chegeni, Razieh; Erevik, Eilin K.; Mentzoni, Rune A.; Pallesen, Ståle (Frontiers in Psychology, 2023)
The present study investigates the longitudinal relationship between problematic gambling (PG) and the five factor model's personality traits using autoregressive crosslagged modelsThe data used in the current study was collected by a national survey in 2013 (n = 10081) and a follow-up study (n = 5848) in 2015. PG was measured using Canadian Problem Gambling Index (CPGI) while personality was assessed using Mini-International Personality Item Pool (MINI-IPIP). Participants who completed the CPGI and all the personality items during both waves (n = 2702) were analysed.The results show that neuroticism had positive cross-lagged associations with CPGI. In contrast, conscientiousness and agreeableness in 2013 were found to have inverse crosslagged effect on CPGI in 2015. Finally, openness and extraversion did not have any crosslagged associations with CPGI.Conclusions: PG poses serious negative implications for the involved individuals as well as their associated close social circle. Hence, it is important to understand predictors of PG for prevention purposes. Personality traits are one of the influential frameworks for examining uncontrolled psychopathological behaviors like PG. The study findings offer significant theoretical as well as practical implications.